2010
DOI: 10.1002/pfi.20175
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate performance: Accelerating expertise in natural settings

Abstract: Deliberate practice—meaning drill‐like practice under the direction of a coach—is key to developing expertise in sports and music. But working professionals and businesspeople typically have no time for practice. We propose deliberate performance as a type of practice that professionals and businesspeople can pursue while they work as a way to accelerate their progression to becoming experts. Four deliberate performance exercises are described: estimation, experimentation, extrapolation, and explanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Consequently, they either purposefully or accidentally form situations nurturing deliberate practices (Ericsson & Charness, 1994) or deliberate performances (Fadde & Klein, 2010) leading to well organized knowledge or mental models that are discussed as one of the indicators of expertise. Two studies from ID literature demonstrated that ID experts utilized their background knowledge and skills related to subject matter and previous experiences regarding the problem that they were trying to provide solutions (Ertmer, et al, 2008;Hardré, Ge & Thomas, 2006).…”
Section: Relationship Between Professional Activities and Mental Modementioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, they either purposefully or accidentally form situations nurturing deliberate practices (Ericsson & Charness, 1994) or deliberate performances (Fadde & Klein, 2010) leading to well organized knowledge or mental models that are discussed as one of the indicators of expertise. Two studies from ID literature demonstrated that ID experts utilized their background knowledge and skills related to subject matter and previous experiences regarding the problem that they were trying to provide solutions (Ertmer, et al, 2008;Hardré, Ge & Thomas, 2006).…”
Section: Relationship Between Professional Activities and Mental Modementioning
confidence: 99%
“…The present study utilized an online survey to reach the experts and professionals so that it was not feasible to collect any other supporting measures which Ericsson and Charness (1994) suggested. However, Fadde and Klein (2010) discussed that deliberate practices are usually more appropriate for psychomotor skills, e.g., playing an instrument, and cannot be easily identified in the jobs requiring knowledge work which all business and professional work are based; therefore, deliberate practice is impractical for business people. They offered deliberate performance, which is thought as the part of routine jobs and just-in training activity, instead of deliberate practice.…”
Section: Relationship Between Professional Activities and Mental Modementioning
confidence: 99%
See 1 more Smart Citation
“…He presented where experts look for picking up predictive information through videos (Fadde, 2010). Fadde and Klein (2010) state professionals such as teachers can gain expertise through extensive job experience. They suggest providing opportunity on four exercises (estimation, experimentation, extrapolation, and explanation) for advanced learners (Fadde & Klein, 2010).…”
Section: Theoretical Base Of the Study: Expertise-based Training (Xbt)mentioning
confidence: 99%
“…They suggest providing opportunity on four exercises (estimation, experimentation, extrapolation, and explanation) for advanced learners (Fadde & Klein, 2010). Fadde and Klein (2010) emphasize the importance of the awareness of resources, and time needed to complete a task; learning from the results the action; having lessons from others' actions; and concluding a result for reflective explanation.…”
Section: Theoretical Base Of the Study: Expertise-based Training (Xbt)mentioning
confidence: 99%